Strategi Pengembangan Bisnis Rumah Makan Padang Di Sekitar Lingkar Kampus IBI Kosgoro 1957 - Reny Andriyanty; Marsadi Aras; Silvia Nur Afuani; Amalia Nurfallah (Mediastima, 2020)
The reseach purpose formulated the specific strategy for Rumah Makan Padang business development. The research method is descriptive qualitative. Data analysis techniques will be divided into three activities: 1) The input stage uses the Delphi technique, 2) the adjustment stage by weighting technique which used a reciprocal rank method and 3) The decision determination stage analyzed by the quantitative strategic planning matrix method. The recomendation strategy are: do the supply chain management with trusted suppliers, make the collaboration with the government to facilate and grant all permits related to halal, health, safety and food security accreditation, develope financing, delivery and promoting throug digital technology, innovate the menus and keep to maintaining unique building concepts and service techniques.